Effect of oxygen tension on chondrocyte extracellular matrix accumulation. - Murphy, C; Sambanis, A (2001)
Since cartilage is mainly an avascular tissue, chondrocytes exist in a low-level oxygen environment in vivo. In the present study, we investigated the effect of oxygen tension (20%, 5% and 1% gas phase oxygen concentrations) over a 20-day period on the extracellular matrix accumulation of bovine articular chondrocytes in confluent surface cultures. Matrix accumulation was assessed by the amount of glycosaminoglycan and collagen deposited in the matrix. From initially confluent monolayers, the chondrocytes became distributed throughout a thick layer of extracellular matrix, thus forming a multicell-layer of tissue. Cells maintained their normal rounded shape, indicative of the differentiated phenotype, throughout the 20-day culture period. On a per culture and a per cell basis, the amount of collagen and glycosaminoglycan accumulation in the matrix was lower at the reduced oxygen tensions. Specifically, in 1% oxygen, matrix GAG content reached a steady-state level, with no net increase in GAG levels after two weeks, whereas in 20% oxygen, matrix GAG increased with time. It is concluded that oxygen has a significant effect on the amount of macromolecules accumulated in the extracellular matrix. The implications of these findings in growing cartilage constructs in vitro are discussed.